Vives and Vitoria on War. Humanism and Scholasticism - Vilarroig Martín, Jaime (Razón y fe, 2025)
Juan Luis Vives and Francisco de Vitoria are two authors who published works on war almost at the same time. Vives in his Concordia et discordia in humano genere (1529) addresses the issue from a humanist and pacifist perspective, while Vitoria, in his relectione of De iure belli (1539), addresses the same problem but from a scholastic perspective, where the justification of an armed intervention is possible. In this article, both works are analyzed looking for points of agreement (for example, the coincidence in bad consequences of war) but also their differences (for example, Vivesian idealism versus the realism of Vitoria).
Keywords: just war; discord; Vives; Vitoria; scholasticism; humanism